إعداد مواد تعليم اللغة - Miftachul Taubah (Universitas Yudharta Pasuruan, 2019)
In this article, we will discuss some of the preparations that must exist in meeting the criteria for making good textbooks to support Arabic language learning. We know from this article that preparation of language teaching materials consists of several elements: 1) Teaching material was created to complement the three elements of learning: teacher, student and subject of learning, 2) Distinguish between teaching language as a mother tongue and a second language, 3) The location of the textbook in the education process, 4) The language that must be taught is the official language of Arabic, 5) Linguistic level in education, 6) The selected text must match the theme, 7) Intermediary language, 8) Students and learning objectives, 9) Culture in languages, 10) Some basics of preparing a book, 11) Building books: unit systems, learning systems, unit and learning systems, and narrative systems, 12) Some companion books, 13) supporting elements in understanding textbooks: teacher guides and dictionaries.